Tool design for low-frequency vibration cutting on surface property - Nakamura, Shogo; Nakanishi, Kenichi; Ohara, Kenji; Nakamura, Yoshikatsu; Ren, Zongwei; Kizaki, Toru; Sugita, Naohiko (Frontiers in Manufacturing Technology, 2023)
Low frequency vibration cutting is a machining technology whereby chips are broken by applying periodic vibrations in a specified axis. Periodic vibration deteriorates the surface roughness and roundness of the workpiece compared with conventional cutting. This study simulated the properties of a machined surface under low frequency vibration. Based on the simulation results, a tool was designed to reduce the effect of periodic vibrations on the surface properties. Actual machining experiments were conducted using the proposed tool to clarify the relationship between the tool shape, surface roughness, and roundness under low frequency vibration. During low frequency vibration cutting with the proposed tool, the surface roughness was reduced from 5.74 µm to 0.94 µm in Ra, and from 23.09 µm to 6.66 µm in Rz, compared with conventional tool. The average roundness with the proposed tool on low frequency vibration is improved from 4.73 µm to 2.95 µm, compared with that of conventional tool. The maximum roundness with the proposed tool is reduced from 15.34 µm to 3.61 µm, compared with that of conventional tool.